On a similarity solution of MHD boundary layer flow over a moving vertical cylinder. (19th September 2006) - Amkadni Amkadni, Maryem Maryem; Azzouzi Azzouzi, Adnane Adnane
Abstract : The steady flow of an incompressible electrically conducting fluid over a semi-infinite moving vertical cylinder in the presence of a uniform transverse magnetic field is analyzed. The partial differential equations governing the flow are reduced to an ordinary differential equation, using the self-similarity transformation. The analysis deals with the existence of an exact solution to the boundary value problem by a shooting method.